Il dibattito degli esperti sul Covid-19: sintomi di decivilizzazione - Giuseppe Tipaldo; Sara Rocutto; Carlotta Merlo; Fabio Bruno (Quaderni di Sociologia, 2022)
In this study we use the Covid-19 pandemic as a revealing case of some emerging dynamics in techno-scientific controversies, opening a dialogue between the STS tradition and Norbert Elias’ theoretical reflection, in particular on the processes of “civilization” and “decivilization”. Our theoretical model is empirically examined by means of a CATA (Computer-Assisted Text Analysis), carried out from data generated by public pages and active users on Facebook Italy in the period January 2020-July 2021 (texts N > 5.5 million) and, to a lesser extent, other media sources (transcripts of TV debates, newspaper interviews, Instagram and Twitter).The analysis shows, first of all, that it is precisely at moments of greatest media interest and on topics where confrontation becomes more acute that the representation of ‘expert’ knowledge reaches the highest peaks of popularity on Facebook. In addition, most of the episodes examined take the form of interdisciplinary conflict, i.e. they function as a rhetorical device operated by members of boundary-pushing scientific disciplines who are in conflict with each other. The competition is not without personal attacks and fallacies of argumentation, even when the debaters are representatives of so-called ‘official’ science. With regard to the effects on the public, traces of hate speech were found in almost a quarter of the comments generated by users: these are accompanied by polarized positions around the pandemic and the ‘experts’, as well as conspiratorial readings of the events. A small but not unnoticeable proportion of the texts manifest cognitive discomfort due to the information overload generated by the personalization of experts who attack and deny each other.We call for more research to understand whether the observed dynamics will consolidate, over time, into a lasting process of decivilization.